Cigarette smoking leads to persistent and dose‐dependent alterations of brain activity and connectivity in anterior insula and anterior cingulate. (25th August 2015) - Zanchi, Davide; Brody, Arthur L.; Montandon, Marie‐Louise; Kopel, Rotem; Emmert, Kirsten; Preti, Maria Giulia; Van De Ville, Dimitri; Haller, Sven
Abstract: Although many smokers try to quit smoking, only about 20–25 percent will achieve abstinence despite 6 months or more of gold‐standard treatment. This low success rate suggests long‐term changes in the brain related to smoking, which remain poorly understood. We compared ex‐smokers to both active smokers and non‐smokers using functional magnetic resonance imaging (fMRI) to explore persistent modifications in brain activity and network organization. This prospective and consecutive study includes 18 non‐smokers (29.5 ± 6.7 years of age, 11 women), 14 smokers (≥10 cigarettes a day >2 years of smoking, 29.3 ± 6.0 years of age, 10 women) and 14 ex‐smokers (>1 year of quitting 30.5 ± 5.7 years of age, 10 women). Participants underwent a block‐design fMRI study contrasting smoking cue with control (neutral cue) videos. Data analyses included task‐related general linear model, seed‐based functional connectivity, voxel‐based morphometry (VBM) of gray matter and tract‐based spatial statistics (TBSS) of white matter. Smoking cue videos versus control videos activated the right anterior insula in ex‐smokers compared with smokers, an effect correlating with cumulative nicotine intake (pack‐years). Moreover, ex‐smokers had a persistent decrease in functional connectivity between right anterior insula and anterior cingulate cortex (ACC) compared with control participants, but similar to active smokers. Potentially confounding alterations in gray or white matter were excluded in VBM and TBSS analyses. In summary, ex‐smokers with long‐term nicotine abstinence have persistent and dose‐dependent brain network changes notably in the right anterior insula and its connection to the ACC. Abstract : Although many smokers try to quit smoking, only a minority archives long‐term abstinence. This indicates smoking‐related long‐term modifications in brain networks, which remain poorly understood. We investigated the neural mechanism mediating long‐term cigarette abstinence by the comparison of ex‐smokers to both active smokers and non‐smokers during a smoking‐cue video fMRI challenge. Ex‐smokers have persistent brain network changes notably in the right anterior insula and its connection to the ACC, an effect correlating with cumulative nicotine intake (pack‐years).